Kepemimpinan Pribadi dan Sosial (Leadership) dalam Perspektif Hadis - Ibnu, Ibnu (Universitas Islam Negeri Raden Intan Lampung, 2017)
The main task of humans as the Caliph on earth, cause consequences for human beings able to account for every action in life. At least, man must be a